2012
DOI: 10.1158/1538-7445.am2012-4435
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4435: Overexpression of Rhotekin confers gastric cancer cells resistance to interferon-α-mediated growth inhibition

Abstract: Tumor infiltrating lymphocytes (TILs) are frequently detected in a variety of malignancies, including gastric cancer (GC). TILs are known to produce high level of interferon-gamma (IFN-γ) in GC, but fail to suppress tumor growth. We have previously shown that Rhotekin (RTKN), the gene encoding the Rho effector RTKN, is overexpressed in human GC, and its expression is correlated with disease progression. In this study, we show that RTKN expression efficiently blocks IFN-γ-mediated anti-growth and immunologic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…RTKN belongs to the group of proteins containing a Rho-binding domain, which are target peptides (effectors) for Rho-GTPases (14). A previous study identified a novel cDNA exhibiting homology with human RTKN, designated RTKN2, and was observed in the cytosol and nucleus of CHO cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…RTKN belongs to the group of proteins containing a Rho-binding domain, which are target peptides (effectors) for Rho-GTPases (14). A previous study identified a novel cDNA exhibiting homology with human RTKN, designated RTKN2, and was observed in the cytosol and nucleus of CHO cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that RTKN promoted upregulation of histone deacetylase 1 to reduce the acetylation level of p53, thus suppressing GC cell cycle pro-gression and apoptosis (Sun et al, 2019). Moreover, RTKN enhanced the resistance of GC cells to interferonα-induced tumour suppression (Yin et al, 2012). This study investigated the effects of RTKN2 on cell proliferation, invasion, migration and radioresistance of GC.…”
Section: Discussionmentioning
confidence: 96%
“… 8 RTKNs are Rho effector proteins, and are expressed in lymphocytes and bone marrow-derived cells, 9 , 16 as well as in lung, colon, thymus, and brain. 17 Two RTKN proteins, RTKN1 and RTKN2, with the same Rho GTPase binding domain, have homologues in mammals. 18 RTKN2 may play a critical role in cell proliferation, apoptosis, and metastasis in many malignant tumor cells.…”
Section: Discussionmentioning
confidence: 99%